2008
DOI: 10.1007/s12237-008-9097-9
|View full text |Cite
|
Sign up to set email alerts
|

Macrofaunal Spatial Patterns in Relationship to Environmental Variables in the Richibucto Estuary, New Brunswick, Canada

Abstract: Estuarine macrobenthos respond to a variety of environmental gradients such as sediment type and salinity, and organic enrichment. A relatively new influence, organic loading from suspended bivalve culture, has the potential to alter this response. A study on soft-bottom macrobenthic communities was carried out in the Richibucto estuary (46°4 0′N, 64°50′W), New Brunswick, Canada, with samples collected from 18 stations in late September and early October 2006. The site consisted of a large tidal channel origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 25 publications
6
34
0
Order By: Relevance
“…The abundance of invertebrates in this study was well within the range described by Shaw (1998) (mean abundance of 135-887 individual/m 2 ) for a comprehensive study of benthic invertebrates in PEI estuaries. The number of taxa found in our study was within the range found by Mallet et al (2006) and Lu et al (2008) at the furthest sampling stations (Tracadie and Lamèque 100 m). All other sites in this study had a lower number of taxa than those of the other studies by Lu et al (2008) and Mallet et al (2006), but those other sites had similar number of species found by Miron et al (2005) where 53% of the station sampled contained less than five species.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The abundance of invertebrates in this study was well within the range described by Shaw (1998) (mean abundance of 135-887 individual/m 2 ) for a comprehensive study of benthic invertebrates in PEI estuaries. The number of taxa found in our study was within the range found by Mallet et al (2006) and Lu et al (2008) at the furthest sampling stations (Tracadie and Lamèque 100 m). All other sites in this study had a lower number of taxa than those of the other studies by Lu et al (2008) and Mallet et al (2006), but those other sites had similar number of species found by Miron et al (2005) where 53% of the station sampled contained less than five species.…”
Section: Resultssupporting
confidence: 84%
“…The number of taxa found in our study was within the range found by Mallet et al (2006) and Lu et al (2008) at the furthest sampling stations (Tracadie and Lamèque 100 m). All other sites in this study had a lower number of taxa than those of the other studies by Lu et al (2008) and Mallet et al (2006), but those other sites had similar number of species found by Miron et al (2005) where 53% of the station sampled contained less than five species. The TOC concentrations we measured (mean 25.3 ± 15 g/kg, n = 7) at both sites were similar to those measured by Parker (2008) (mean 22.4 ± 12.1 g/kg) at proximal sites.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations